Pengaruh Tingkat Pengangguran Terhadap Tingkat Kemiskinan Kabupaten/Kota Di Provinsi Bali - Syafitri, Annisa; Aulia, Nadia Restu; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2022)
The purpose of this study was to determine the effect of unemployment on poverty in districts/cities in Bali Province. This study tested the hypothesis of 2 (two) research periods of 2 (two) years, from 2020 to 2021 using panel data in the form of time series data (2020-2021) and cross sections (8 districts/cities) in Bali Province. Analysis of this regression model using SPSS. Based on the test results with a significance level of = 0.05, there is no significant relationship between the unemployment rate and the poverty rate, with a t value of 0.017 > 0.05m indicating a unidirectional (positive) relationship.